Moderating Role of Feedback Methods in Customer-Centric Innovation Adoption: Evidence on Micro and Small Enterprises in Cavite, Philippines - Xavier Lawrence Mendoza; Nerisa B Abug (International Journal of Entrepreneurship, Business, and Creative Economy, 2025)
This study investigates the role of customer feedback methods on the behavioral intention to adopt customer-centric innovation among micro and small enterprises (MSEs) in Cavite, Philippines. Using a predictive-causal research design and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study examines the relationships between customer ideas, organizational beliefs and values, enterprise resources, feedback methods, and behavioral intention to adopt customer-centric innovation. Data were collected from 125 MSEs in select municipalities of Cavite. Results confirm the positive impact of customer ideas, organizational beliefs and values, and resources on innovation adoption intention. Generally, the study reveals a moderating role of feedback methods. While feedback strengthens the link between customer ideas and intention to adopt customer-centric innovation, it negatively impacts the relationship between enterprise resources and intention. The study highlights the importance of strategically designed, lean, and actionable feedback mechanisms for MSEs, emphasizing the need for alignment with business size and resource availability.These findings contribute to the literature on innovation management in developing economies and offer practical insights for entrepreneurs and policymakers supporting MSEs.